“A child with severe pneumonia cannot feed, causing malnutrition”: exploring health worker and caregiver perspectives and practices for mitigating malnutrition among children with severe pneumonia, a case of Uganda - Damalie Nalwanga; Robert Opika Opoka; Andrew Sentoogo Ssemata; Lawrence Kakooza; Andrew Kiggwe; Victor Musiime; Sarah Kiguli (BMC Health Services Research)
Abstract Background Severe pneumonia remains the leading cause of morbidity and mortality among children worldwide. Severe pneumonia causes death during hospitalization, and survivors are prone to malnutrition after discharge from the hospital. The World Health Organization and United Nations International Children’s Fund recommend ‘continued’ feeding following a severe pneumonia illness without specific recommendations on nutritional support. This recommendation could influence health workers’ and caregivers’ nutritional practices. This study aimed to explore the perspectives and practices of health workers and caregivers for mitigating malnutrition among children with severe pneumonia. Methods We conducted a cross-sectional qualitative study between June and November 2021 among health workers and caregivers of children hospitalized with severe pneumonia at Mulago National Referral Hospital in Kampala, Uganda. The data were collected via focus group discussions involving 17 caregivers and key informant interviews with 12 health workers and were analyzed via the content-thematic analysis approach. Both manual coding and Atlas Ti software were used to support the analysis. Results Health workers and some caregivers were aware that severe pneumonia predisposes children to malnutrition to various degrees, citing reduced appetite, difficulty breathing, persistent vomiting, and increased metabolic demands as pathways. Caregivers increased breastfeeding and utilized nutrient-rich foods to prevent malnutrition, while health workers applied caregiver education and tailored pneumonia management strategies, including following available guidelines and working with nutritionists. Conclusion Severe pneumonia is recognized among health workers and some caregivers as a risk factor for malnutrition. However, mitigating strategies are not uniformly practiced by caregivers and could be enhanced by effective health education and sensitization. More specific guidelines could further reinforce the beneficial practices of health workers managing children with severe pneumonia who are not severely malnourished, and improve treatment outcomes.